2013
DOI: 10.1161/circep.113.000869
|View full text |Cite
|
Sign up to set email alerts
|

Renal Dysfunction, Stroke Risk Scores (CHADS 2 , CHA 2 DS 2 -VASc, and R 2 CHADS 2 ), and the Risk of Thromboembolic Events After Catheter Ablation of Atrial Fibrillation

Abstract: Background-There are limited data on the predictive value of stroke risk scores for thromboembolic events (TEs) after catheter ablation of atrial fibrillation (AF). Our objectives were to report the incidence of TEs after AF ablation in a large contemporary AF ablation cohort and to investigate the impact of renal dysfunction and the value of stroke risk stratification scores (CHADS 2 , CHA 2 DS 2 -VASc, and R 2 CHADS 2 ) for predicting TE after AF ablation. Methods and Results-Using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Therefore, it seems that the CHA 2 DS 2 -VASc scoring system is more sensitive (than CHADS 2 ) for assessment of thromboembolic risk after catheter ablation of AF. Recently, another study confirmed these results [157]. During the 18-month follow-up after the procedure the prevalence of thromboembolic events was 0.72%.…”
Section: Thromboembolic Complications Preprocedural Thrombosis Tranmentioning
confidence: 66%
See 2 more Smart Citations
“…Therefore, it seems that the CHA 2 DS 2 -VASc scoring system is more sensitive (than CHADS 2 ) for assessment of thromboembolic risk after catheter ablation of AF. Recently, another study confirmed these results [157]. During the 18-month follow-up after the procedure the prevalence of thromboembolic events was 0.72%.…”
Section: Thromboembolic Complications Preprocedural Thrombosis Tranmentioning
confidence: 66%
“…The risk was only 0.13% with a CHA 2 DS 2 -VASc score of 0-1 and 0.71% with a CHA 2 DS 2 -VASc score of >2. In addition, it seems that the CHA 2 DS 2 -VASc score has the best predictive value in patients with AF recurrence after catheter ablation [157].…”
Section: Thromboembolic Complications Preprocedural Thrombosis Tranmentioning
confidence: 98%
See 1 more Smart Citation
“…9,10 The activation of the clotting system is another critical issue, which is related to the duration of the RF procedure and concurs to asymptomatic cerebral emboli. 8,11 In this issue of Circulation, Stazzi et al 12 address the question as to whether platelet activation is also implicated in the prothrombotic state occurring after RF ablation and if remote ischemic preconditioning (IPC) is able to prevent it.…”
Section: Article See P 11mentioning
confidence: 99%
“…Since many of the clinical factors included in the most common stroke risk prediction instruments 2, 3 , CHADS2, and CHA2DS2-VASc, are also associated with development of AF 4, 5 , several studies have examined the predictive capacities of these same instruments for recurrent AF after PVI. Unfortunately, although CHADS2 and CHA2DS2-VASc show excellent performance for stroke prediction, they demonstrate only modest discriminative ability with respect to identifying individuals at risk for AF recurrence after PVI 6-9 .…”
Section: Introductionmentioning
confidence: 99%